BIMBINGAN TEKNIS TATA KELOLA PENDIRIAN PUSAT KEGIATAN BELAJAR MASYARAKAT (PKBM) DAARUT TAUHID MELALUI ONLINE SINGLE SUBMISSION (OSS) - Dadang Yunus Lutfiansyach; Mustofa Kamil; Jajat S. Ardiwinata (IKIP Siliwangi, 2022)
Online Single Submittion (OSS) is a business license issued by the OSS institution through an electronically integrated business service system in an easy, faster, precise and efficient way. The purpose of this study is to describe data regarding the implementation of the OSS system in PKBM Daarut Tauhiid. The theoretical studies used in this research are the concept of mentoring, the concept of Community Learning Activity Center and Online Single Submittion (OSS). The method used in this research is descriptive method with data collection techniques in the form of interviews and literature studies. The results showed that the implementation of OSS in PKBM Daarut Tauhiid went through the following steps; First, log in to the OSS system using the user-ID that was created previously. Second, fill in the required data including company data, product data, business data related to the establishment of PKBM buildings and also workers. Third, fill in the business field information in accordance with the Indonesian Standard Clarification for Business Fields (KBLI). The description that is filled in in the establishment of PKBM is a description of the business field of the Daarut Tauhiid PKBM non-formal unit. and fifth, business actors will get NIB.